Prognostic Impact of Decline in Platelet Count in Underwent in PCI (Journal of Medical & Health Sciences Review, 2025)
Background: Reduced platelet count after PCI has occurred as a potential predictor of patients’ outcomes over the past few years. Defining post-PCI platelet count reduction as above, a significant relationship between post-PCI platelet reduction and adverse clinical events such as bleeding, thrombocytopenia and higher mortality was observed.Objective: The purpose of this research was to determine the significance of platelet count reduction for the prognosis of PCI patients.Methods:  This prospective analysis was carried out at Department of Cardiology, PAEC Hospital,  Islamabad,  from 1st August 2024 till 31st December 2024. The study included 213 patients with CAD who underwent PCI. The inclusion criteria included that patients were ≥18 years of age. Secondary end points were BARC adjudicated bleeding events and all-cause mortality. Gastrointestinal bleeding was categorized as minor (BARC types 1 and 2), and major (BARC types 3 and 5)Results: The mean age of the participants was 63.2 ± 10.5 years, with males contributed to (71.8%). The most frequent coexisting conditions were hypertension in (52.6%) of cases and diabetes mellitus in (37.1%) of cases; there was no significant difference in the prevalence of comorbidities among the groups (p=0.653, p=0.950, respectively). MI was in the significant decline group (27.9%) as compared with moderate (10.2%) and minimal decline groups (5.6%), p < 0.01.Conclusions: According to our study, larger post-PCI drop in platelet count is related to increased risk of MI, ST, TVR, major bleeding events and death. These results suggest that platelet count should be checked periodically and appropriate interventions should be offered to enhance patient’s prognosis.